Return on Education : Measuring the Benefits, Challenges, and Strategies for Optimizing Education Investment - Ike Laura Krisna; Ani Widayati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Education is widely recognized as a crucial investment with significant economic and social benefits. This study employs a bibliometric approach to analyze trends, influential works, and research patterns related to Return on Education (RoE). Using Google Scholar as the primary data source, publication metadata were retrieved and analyzed with VOSviewer to visualize co-authorship networks, keyword co-occurrences, and citation relationships. The findings indicate an increasing research focus on RoE, particularly in areas concerning economic returns, labor market alignment, and educational policy optimization. The keyword analysis highlights the importance of skill development, policy adaptation, and industry collaboration in maximizing educational returns. Additionally, citation network analysis reveals the most influential studies shaping this field. Despite its contributions, this study acknowledges limitations in data completeness due to Google Scholar’s metadata constraints. The insights derived from this analysis provide valuable guidance for policymakers, educators, and researchers in enhancing the effectiveness of educational investments.